How to overcome pitfalls of (E)ER and UML in Knowledge Management education. (2nd July 2008) - Bollen, Peter
In this paper we will present the results of research into modelling pitfalls in (Extended) Entity Relationship modelling ((E)ER) and the Unified Modelling Language (UML). We will give a precise definition of the relationship cardinality/association end multiplicity concept in (E)ER and UML based upon the various definition 'fragments' we have encountered in the (E)ER and UML literature and we will give explicit rules for the application of these constructs for Knowledge Management (KM) in an educational setting.